Attempted suspect-provoked shootings in Victoria: prevalence and characteristics. Issue 4 (20th November 2017) - Kesic, Dragana; Thomas, Stuart
Abstract : Purpose: The purpose of this paper is to examine the prevalence of attempted suspect-provoked shootings (SPS) in Victoria, Australia, and explore nonlethal tactics police officers use to resolve such incidents. Design/methodology/approach: A random sample of 20 percent of police-attended incidents was sourced from a police contact-based database. The narrative of each incident was coded using established criteria for "suicide-by-cop." Incidents that met the criteria were further analyzed to elucidate historical and situational characteristics. To supplement these data, operational police officers were invited to participate in a survey about particulars of an attempted SPS incident that they had attended and resolved non-fatally. Findings: Police are encountering these incidents up to three times a week in Victoria, Australia. While they engage in a range of tactics, police report that communication and negotiation skills are the most effective means of successful resolution. Research limitations/implications: Although the survey attempted to correct for the potential limitations of using administrative data for research purposes, its weakness is in the modest sample size that utilizes self-report data that may lead to recall biases. Further research would benefit from using complementary methodologies that seek to examine police tactics and elucidate decision-making processes using video-based or written vignettes. Practical implications: Officers' awareness of both the commonalty of this phenomenon and of the important situational characteristics may lead to greater skill and confidence in managing these. Originality/value: This is one of the very few published studies investigating prevalence and characteristics of attempted SPS incidents.